Editorial - Melba L. Cárdenas (Asociación Colombiana de Profesores de Ingles, 2016)
Welcome to the second edition of our twenty-third volume. It comes out within the expectations the new indexing policies issued by Publindex-Colciencias has generated. The Colombian research agency that monitors the academic journals published in the country is about to launch the changes in the parameters that will be borne in mind for ranking purposes. They will most likely insist on the visibility of the journals in the Journal Citation Reports (JCR), led by Thomson and the Scientific Journal Ranking (SJR), managed by Scopus. Both of them measure the journals' impact on the citations received in prestigious publications. Whether or not we can fulfil the coming policies, our commitment to maintain HOW open to local and international scholars' projects remains as the main driving force to publish ASOCOPI's (Asociación Colombiana de Profesores de Inglés) journal.